Da’wah Strategy for Disabilities People in the Covid-19 Pandemic Era - Mutrofin Mutrofin (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
This article attempts to explore various problems faced by people with disabilities in the pandemic era. Da'wah is more than just Amar Ma'ruf Nahi Munkar (perform good and keep away from bad). The study of da'wah is not just about conveying Islamic treatizes but keeping up with the times. Dilemmas that arise in the community must find immediate solutions, especially those related to basic needs. The methods and models of da'wah must adapt to the current da'wah models. The appropriate da'wah model for groups with disabilities in the new normal is the da'wah bil maal method (a missionary endeavour using wealth, such as giving money to the poor). This study adopts a qualitative method and draws samples from five informants. The informants are from the disability group, especially those who are married. The data was collected using in-depth interviews. This study aims to increase awareness of the importance of mutual respect and mutual assistance among people.